Blogging revisited: the use of blogs in ESAP courser - Nicolaou, Anna; Kakoulli-Constantinou, Elis (My University, 2014)
The technological innovations of the last decades and the appearance of the Web 2.0 have triggered various advancements in the field of education in general and language teaching and learning in particular. The weblog or blog is nowadays one of the most popular Information Communication Technology (ICT) tools used for educational purposes, thus research on the use of blogs in education has seen increasing interest. This paper examines blogging as a learning tool in the instruction of English for Specific Academic Purposes (ESAP) in tertiary education. It explores the possibilities and pedagogical value offered by using weblogs in language learning, as well as university students’ attitudes towards the use of blogs in their language courses.
Keywords: Blogs; Language learning; Language teaching; ESAP; ICT; CMC; BALL; New technologies